Claudette Colvin : Twice Toward Justice - Hoose, Phillip M. 1947- (New York : Melanie Kroupa Books, 2009)
Presents the life of the Alabama teenager who played an integral but little-known role in the Montgomery bus strike of 1955-1956, once by refusing to give up a bus seat, and again, by becoming a plaintiff in the landmark civil rights case against the bus company.
Includes bibliographical references and index.
Keywords: Colvin, Claudette, -- 1939-; African Americans -- Biography -- Montgomery (Ala.); Civil rights -- Biography -- Montgomery (Ala.); African Americans -- Civil rights -- Montgomery (Ala.); Segregation in transportation -- History -- Montgomery (Ala.); Women -- Biography; Montgomery (Ala.) -- Biography; Montgomery (Ala.) -- Race relations